Uso de harina de ajo (Allium sativum) y harina de cúrcuma (Curcuma longa) como aditivos alimenticios en la dieta de pollos Broiler - Narváez Chandi, Jeovanna Salomé (2024)
The following research work presents the use of garlic flour and turmeric flour as food additives in the diet of Broiler chickens, this is an alternative for productive improvement, using natural and non-synthetic ingredients as growth promoters. The objective of the study was to evaluate the different treatments used and identify the most optimal one based on the productive behavior of the chickens, in addition to an analysis of the cost and benefit of the use of these additives in their feed. In this study, 120 one-day-old Broiler chickens were used, which were randomly distributed into 4 different groups with 30 chickens in each one and 3 repetitions per group. The 4 treatments used consisted only of balanced (Control), balanced + 0.5% garlic flour + 0.5% turmeric flour (Treatment 1), balanced + 1% garlic flour + 1% turmeric flour (Treatment 2), balanced + 1.25% garlic flour + 1, 25% turmeric flour (Treatment 3). The properties and nutritional composition of garlic flour and turmeric flour were investigated since these ingredients were of commercial origin\; As the research was descriptive-experimental, data on productive behavior was collected daily, such as weekly weight, feed consumption, weight gain, feed conversion and finally in the last stage the incidence of coccidia in the intestine was verified. and in feces, from a coprological examination and the sacrifice of 4 chickens, one per treatment. To establish the effectiveness of the most optimal treatment, the ANOVA and the Tukey test at 5% were used, in this way the differences between each treatment and its effectiveness in productivity were found.